Determinants and market performance of Fortune 100 best companies: evidence from Islamic perspective - Bhaskaran, Rajesh Kumar; Ting, Irene Wei Kiong; Noor Azlinna, Azizan; Yelubolu, Kranti (Emerald Publishing Limited, 2021)
Purpose – Islam is valid for every place and time, and it promotes fair and equitable employees’ relations as an essential corporate social responsibility (CSR) policy for successful organisations such as Fortune 100 companies. Whence, this study aims to explore Fortune 100 best companies exhibit better market performance and capitalisation relative to other companies in relation to their employees’ satisfaction as a significant contributor to better performance. Design/methodology/approach – This study conducts two-stage robust least square regressions analyses on Fortune’s best a sample of Fortune companies list in 2017. Findings – Tests of differences in mean indicate that Fortune listed companies have superior profitability, liquidity and firm size compared with the control sample data set. The regression results are also robust to the use of different measures of market performance, such as market capitalisation, price/earnings ratio and price/book ratio, as well as to the potential endogeneity problem. This study also reveals the top 10 employers with the highest number of employees with their number of times being ranked in Fortune best companies. The result is in line and compatible with the concept of CSR in Islam perspective which encompasses legal, economic, ethical and philanthropic responsibilities (Maruf, 2013). Islamic CSR promotes the behaviour of brotherhood and justice to balance employee rights and better coherence between self-interest and altruism. With that, satisfied employees contribute to firm performance. Practical implications – Overall, this study extends the insight that satisfied employees may, in turn, mean better market performances for a company. Originality/value – The findings corroborate human relations theories, as well as from the Islamic perspective, employee satisfaction results in greater market performances